A strategy for ammonia odor monitoring, prediction, and reduction from livestock manure wastes in Korea: a short review. Issue 1 (4th March 2022) - Lee, Sang-Hun; Bae, Sunghyun
ABSTRACT: Ammonia is a malodorous substance, even at low concentrations, that has harmful effects on humans and the environment. Ammonia is considered an alternative energy source for hydrogen energy transport. Most ammonia is emitted from livestock facilities, as the main sources of ammonia odor. Therefore, this study focused on the emission and dispersion of ammonia as the main compound in ammoniacal odor substances from livestock manure facilities, as well as on the treatment and recovery of ammonia near livestock facilities. First, this study reviewed the monitoring of ammoniacal odor recommended by multiple low-cost monitoring sensors integrated with information technology (IT). To enhance the monitoring data quality, periodic calibration and validation through reference instruments is essential. To estimate odor emissions, emission factors should be classified by considering various scenarios and conditions. The application of modelling is desirable for predicting the dispersion of ammonia and odors, but a simpler model should be developed for non-experts in the preliminary stage. For ammonia treatment and resource recovery, it is necessary to support the development of high-efficiency and eco-friendly treatment technologies, which should be tested in upscaled systems with actual odors under field conditions.